2011
DOI: 10.1299/jee.6.426
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cavitation with Microphone Placed Outside Piping

Abstract: Cavitation-induced vibration and erosion of pipes are potential damaging factors in piping systems. To prevent damage, it is necessary to develop the detection method for cavitation phenomena. In power plants, it is especially desirable to detect their occurrence from outside the piping during operation. In this paper, detection of cavitation phenomena was experimentally investigated using microphones placed outside the piping at positions upstream and downstream from an orifice. The following results were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…However, the flow distributions were different between the orifice and valves; consequently, the locations where the bubbles reached near the pipe wall were different for each pipe component. In the experiments with the orifice, super cavitation appeared below σ=0.5 [8] , and cavitation bubbles did not develop over 2.0 D downstream from the orifice (cf. Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the flow distributions were different between the orifice and valves; consequently, the locations where the bubbles reached near the pipe wall were different for each pipe component. In the experiments with the orifice, super cavitation appeared below σ=0.5 [8] , and cavitation bubbles did not develop over 2.0 D downstream from the orifice (cf. Fig.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously carried out vibration measurements using accelerometers mounted on the outer surface of pipes, and we confirmed that cavitation occurrence could be detected by comparing accelerometer outputs upstream and downstream [7] . Moreover, considering applicability to actual plants, we examined a cavitation detection method using microphones as a noncontact technique [8] [9] and confirmed that microphones could detect a developed cavitation state. However, the cavitation detection characteristic with microphones was inferior to that with the accelerometer, and it was difficult to judge a weak cavitation state.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, these methods are for detecting cavitation in a pump, and studies on cavitation detection at valves and orifices in an operating plant have not been reported. Therefore, we have investigated cavitation detection methods in operating power plants, and we developed the method which compares accelerometer or microphone outputs upstream and downstream from a pipe throttle (5)(6) . However, this method can detect only the stage of developed cavitation under low cavitation numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the average value of the maximum forces, F 1st , in Fig. 10 with erosion pit occurrence in Table 1 showed that there was a minimum force to make erosion pits, and it was about 2 N. Figure 13 compares results of the erosion experiments with cavitation detection characteristics using accelerometers (5) and non-directional microphones (6) …”
mentioning
confidence: 99%